The Development of Essence of Local Learning in Art Key Learning Area on Cage Handicraft for the Sixth Level Elementary Education Students. - Wisapan, Sasithon (Fine Arts Journal: Srinakharinwirot University, 2011)
This study aims to develop the essence of local learning in art for students at a basic level education (grade-6 in particular). The research encompassed three major aspects of work, i.e.: (a) to survey the knowledge of the folk wisdom on “cage handicraft” and related to the topic, (b) to design a lesson plan for that target group of students in art subjects, (c) to implement a lesson plan and evaluated on the bases of students achievement of students of Banna School, Chana District, Songkhla Province by comparing between pre-and posttest scores, and of students’ opinions. The research found that : (a) scores differences of the pre-and posttest were statistically significance (at p<.05) showing students improvement in achievement (b) students were satisfied ; they can use the essence of local learning in daily life and it would be a future carrier for them. การพัฒนาสาระการเรียนรู้ท้องถิ่น กลุ่มสาระการเรียนรู้ศิลปะ เรื่อง หัตถกรรมกรงนกเขาชวา สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 การวิจัยในครั้งนี้ มีจุดมุ่งหมายเพื่อพัฒนาสาระการเรียนรู้ท้องถิ่น กลุ่มสาระการเรียนรู้ศิลปะ เรื่อง หัตถกรรมกรง นกเขาชวา สำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 มีจุดมุ่งหมายเฉพาะ ดังนี้ 1) เพื่อเปรียบเทียบผลสัมฤทธิ์ทางการเรียนของนักเรียนก่อนเรียนกับหลังเรียนสาระการเรียนรู้ท้องถิ่น เรื่อง หัตถกรรมกรงนกเขาชวา 2) เพื่อศึกษาความคิดเห็นของนักเรียนชั้นประถมศึกษาปีที่ 6 หลังจากใช้สาระการเรียนรู้ท้องถิ่น เรื่อง หัตถกรรมกรงนกเขาชวา ขั้นตอนดำเนินการวิจัยมี3 ขั้นตอน คือ 1) การศึกษาข้อมูลพื้นฐาน 2) การพัฒนาสาระการเรียนรู้ท้องถิ่น และ 3) การทดลองใช้สาระการเรียนรู้ท้องถิ่น กลุ่มตัวอย่างที่ใช้ในการทดลอง คือ นักเรียนชั้นประถมศึกษาปีที่ 6 โรงเรียน บ้านนา อำเภอจะนะ จังหวัดสงขลา ผลการวิจัย พบว่า ค่าเฉลี่ยของคะแนนผลสัมฤทธิ์ทางการเรียน หลังเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทาง สถิติที่ระดับ .05 และนักเรียนมีความคิดเห็นว่า มีความรู้เกี่ยวกับหัตถกรรมกรงเขาชวาเพิ่มขึ้น ภาคภูมิใจในภูมิปัญญาของ ท้องถิ่นตนเอง สามารถนำไปใช้ในชีวิตประจำวันและส่งเสริมเป็นอาชีพได้